Bringing positional processes back in: occupational gender segregation in 'non-academic' work. Issue 21 (30th November 2021) - Anderson, Pauline; O'Hagan, Angela; Thomson, Emily
Abstract: This article highlights that organisations mask a 'gendered substructure' and a 'positional substructure', and reinforces the importance of (re)incorporating the effects of positional processes as an analytical concern in current analysis of occupational segregation. Drawing on the concept of 'inequality regimes', we use the case of 'non-academic' workers in Scottish higher education institutions as the context in which to explore how gendered and positional processes may be perpetuating occupational gender segregation—focusing on finance, registry, security and cleaning staff. Our findings show how embedded gendered and positional processes are reinforcing occupational gender segregation in many areas of non-academic work. We reveal that some gendered processes are position-sensitive and that stereotyped language use and related biases impact the progression and treatment of workers at the 'bottom'—and the compounding effects on women. We show that positions within organisational opportunity structures cannot merely be read off grading hierarchies and argue that any analysis of positional substructures necessitates uncovering the potential existence of multiple organisational hierarchies and other forms of positional advantage/disadvantage, whilst recognising that positional substructures are not static.